BIOM-44. MAGNETIC RESONANCE IMAGING MAPPING OF BRAIN TUMOR BURDEN TO EVALUATE RESPONSE TO PULSED LOW-DOSE-RATE RADIOTHERAPY FOLLOWING RESECTION OF GLIOBLASTOMA MULTIFORME: A 4-PATIENT CASE SERIES. (14th November 2022) - Amidon, Ryan; Prah, Melissa; Straza, Michael; Santos-Pinheiro, Fernando; Bovi, Joseph; Schultz, Christopher; Schmainda, Kathleen
Abstract: BACKGROUND: Pulsed low-dose-rate radiotherapy (pLDR) is an accepted reirradiation technique for recurrent glioma, but its upfront use, concurrent with temozolomide (TMZ) following resection of high-grade glioma is currently under investigation. Evaluating the response to upfront radiation can be challenging and there is limited data on expected rates of pseudoprogression with pLDR. Standard magnetic resonance imaging (MRI) has limitations in differentiating pseudoprogression from tumor progression, sometimes necessitating surgery for pathologic confirmation. Advanced MRI can be used to create fractional tumor burden (FTB) maps that spatially distinguish active tumor from treatment-related effect (pseudoprogression), perhaps providing a more reliable imaging biomarker in the absence of additional surgery. METHODS: We performed a retrospective chart review to report the responses of four patients with glioblastoma to upfront pLDR and TMZ following resection. Each patient received advanced surveillance MRI and redo surgery. Tumor pathology included IDH-wild type (n = 4) and O 6 -methylguanine-DNA methyltransferase (MGMT) methylated (n = 1) tumors. RESULTS: The median age of patients was 57.5 years (range 55-60 years) and all were male. One patient experienced mortality and another was transitioned to hospice. In all four cases, there were concerns of tumor progression in postcontrast MRI. Pathologic diagnosis revealed either treatment effect (n = 2) or tumor (n = 2). FTB maps were predominantly indicative of lesion volumes being comprised of treatment effect (n = 3) and tumor (n = 1). From the three FTB maps in the former category, the median fraction of the enhancing tumor volume comprised of vascular tumor was 6.4% (range 1.8-6.8%). CONCLUSION: This case series provides insight into response to upfront pLDR and TMZ following resection of glioblastoma and demonstrates the capacity for FTB mapping to spatially distinguish tumor progression from treatment effect in this patient population.